2020
DOI: 10.1002/ange.201914417
|View full text |Cite
|
Sign up to set email alerts
|

Graphitic Carbon Nitride (g‐C3N4): An Interface Enabler for Solid‐State Lithium Metal Batteries

Abstract: Solid‐state Li metal batteries (SSLMBs) have attracted considerable interests due to their promising energy density as well as high safety. However, the realization of a well‐matched Li metal/solid‐state electrolyte (SSE) interface remains challenging. Herein, we report g‐C3N4 as a new interface enabler. We discover that introducing g‐C3N4 into Li metal can not only convert the Li metal/garnet‐type SSE interface from point contact to intimate contact but also greatly enhance the capability to suppress the dend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 57 publications
(30 reference statements)
1
35
0
Order By: Relevance
“…68 First principle calculation shows that Li-Li 2 CO 3 only has 0.1 J m −2 of interfacial work of adhesion, W ad , whereas that for Li-LLZO is 0.67 J m −2 . Interestingly, the reported contact angle of Li-LLZO varies from 90°to 122°, 64,67,[69][70][71] possibly due to the difference and cleanliness of the surface. Therefore, a standardized measurement procedure, including the precise surface cleaning procedure is required to enable comparison in literature.…”
Section: Garnet/li Interfacementioning
confidence: 99%
See 1 more Smart Citation
“…68 First principle calculation shows that Li-Li 2 CO 3 only has 0.1 J m −2 of interfacial work of adhesion, W ad , whereas that for Li-LLZO is 0.67 J m −2 . Interestingly, the reported contact angle of Li-LLZO varies from 90°to 122°, 64,67,[69][70][71] possibly due to the difference and cleanliness of the surface. Therefore, a standardized measurement procedure, including the precise surface cleaning procedure is required to enable comparison in literature.…”
Section: Garnet/li Interfacementioning
confidence: 99%
“…12 The most representative example is atomic layer deposition (ALD) of Al 2 O 3 on LLZO electrolyte. 64 The ALD method maximizes the contact between Al 2 O 3 and LLZO. Al 2 O 3 is lithiophilic, showing a much smaller contact angle with molten Li (Figure 10B).…”
Section: Toward Garnet/li Interface Aspectsmentioning
confidence: 99%
“…27 c) and maintained a strong/intimate contact with the Garnet (Fig. 27 d) [ 165 ]. Lu et al also reported the application of mesoporous carbon nitride (MCN) and acetylene black (AB) as a support for in situ growth of Pt nanoparticles for an all-solid-state lithium air battery system.…”
Section: Electrochemical Studies Of Cnbms For Energy Storage Devicesmentioning
confidence: 99%
“…Reproduced with permission from Ref. [ 165 ]. e Scheme of the configuration of the MCN-based electrode solid-state lithium-air battery.…”
Section: Electrochemical Studies Of Cnbms For Energy Storage Devicesmentioning
confidence: 99%
“…Meanwhile, good wetting is still maintained after cell cycling as presented in Figure S7 , indicating the stable interface between liquid metals and current collectors. 43 In contrast, when stainless steel was adopted, the liquid metal will ball up on the current collector with poor wetting ( Figure S8 ). The voltage profiles in Figure S9 also show more obvious polarization with a larger overpotential.…”
mentioning
confidence: 99%